HELP!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!
![HELP class=](https://us-static.z-dn.net/files/d97/59d9d2e85bf89788ef1b4dc1f5a7a21d.png)
Answer:
A. 38
Step-by-step explanation:
180- 114 = 66
66 + 2x + x = 180
66 + 3x = 180
-66 -66
3x = 114
— —-
3 3
x = 38
We have that 114° + y is equal to 180°, so,
114° + y = 180°
y = 180° - 114°
y = 66°
And since every triangle has the sum of 180° in the three angles we can say that
66° + 2x + x = 180°
3x = 180° - 66°
3x = 114°
x = 114°/3
x = 38°